Gender differences in clinical presentation and illicit substance use during first episode psychosis: a natural language processing, electronic case register study. Issue 4 (20th April 2021) - Irving, Jessica; Colling, Craig; Shetty, Hitesh; Pritchard, Megan; Stewart, Robert; Fusar-Poli, Paolo; McGuire, Philip; Patel, Rashmi
Abstract : Objective: To determine whether gender differences in symptom presentation at first episode psychosis (FEP) remain even when controlling for substance use, age and ethnicity, using natural language processing applied to electronic health records (EHRs). Design, setting and participants: Data were extracted from EHRs of 3350 people (62% male patients) who had presented to the South London and Maudsley NHS Trust with a FEP between 1 April 2007 and 31 March 2017. Logistic regression was used to examine gender differences in the presentation of positive, negative, depressive, mania and disorganisation symptoms. Exposure(s) (for observational studies): Gender (male vs female). Main outcome(s) and measure(s): Presence of positive, negative, depressive, mania and disorganisation symptoms at initial clinical presentation. Results: Eight symptoms were significantly more prevalent in men (poverty of thought, negative symptoms, social withdrawal, poverty of speech, aggression, grandiosity, paranoia and agitation). Conversely, tearfulness, low energy, reduced appetite, low mood, pressured speech, mood instability, flight of ideas, guilt, mutism, insomnia, poor concentration, tangentiality and elation were more prevalent in women than men. Negative symptoms were more common among men (OR 1.85, 95% CI 1.33 to 2.62) and depressive and manic symptoms more common among women (OR 0.30, 95% CI 0.26 to 0.35). After adjustment for illicit substance use, the strength of associations between gender and negative, manic and depression symptoms increased, whereas gender differences in aggression, agitation, paranoia and grandiosity became insignificant. Conclusions: There are clear gender differences in the clinical presentation of FEP. Our findings suggest that gender can have a substantial influence on the nature of clinical presentation in people with psychosis, and that this is only partly explained by exposure to illicit substance use.